ANALISIS PENERAPAN TARIF PERBANDINGAN PAJAK PENGHASILAN BERDASARKAN PERATURAN PEMERINTAH 46 TAHUN 2013 DAN UNDANG-UNDANG NO 36 TAHUN 2008 UD. BAROKAH TAHUN 2014 – 2017 DI GRESIK - Venanda, Yohana Reienha Satyara; Antoni, Antoni (JEA17: Jurnal Ekonomi Akuntansi, 2020)
ABSTRACTYohana Reienha, 15013061,  Analysis of Application of Comparison of Income Tax Rates Based on Government Regulation 46 of 2013 And Law No 36of 2008 in UD. Barokah of 2014-2017. This research is based on the Government's program in collaboration with DJP that involve UMKM  in Indonesia. This study aims to help each another UMKM in completing its tax administration obligations, especially at UD. Barokah Gresik. To find out the Income Tax calculation using PP 46 of 2013 and Law 36 of 2008 and calculate the more profitable company UD. This Barokah. This type of research is descriptive comparative. Data collection techniques carried out in this study were interviews, documentation and observation. The object in this study is accounting in UD. Barokah. The data analysis technique used is analyzing gross circulation and income statements for 2014-2017, calculating and analyzing the reporting of the payable income tax. The results of this study indicate that the results of the comparison of large PPh payable UD. Barokah Gresik in 2014-2017 if using PP 46 of 2013, the result is a tax payable is smaller than using the rules of Law 36 of 2008. Due to PPh rates owed PP 46 of 2013 is directly charged to the monthly turnover of taxpayers, then every month they pay the tax payable not too big.